An evaluation of anifrolumab for use in adults with systemic lupus erythematosus. (2nd November 2022) - Ahmed, Abdullah Ali; Osman, Naureen; Furie, Richard
ABSTRACT: Introduction: Type 1 interferons play a key role in the pathogenesis of systemic lupus erythematosus (SLE). An important clinical question is whether inhibiting the type 1 interferon pathway reduce the disease activity in SLE patients. This review evaluates the safety and efficacy of the monoclonal antibody against the type 1 interferon alpha receptor, anifrolumab, in patients with SLE. Areas covered: Key terms (SLE, type 1 interferon, anifrolumab) were used to query the PubMed database for phase 1, 2 and 3 clinical trials of anifrolumab for SLE patients. Phase 1 studies showed anifrolumab has non-linear pharmacokinetics and the optimal safe dose is 300 mg given intravenously every four weeks. The MUSE (phase 2) and the TULIP-2 (phase 3) trials showed that anifrolumab when added to standard therapy significantly reduced disease activity in SLE patients. Common adverse events associated with anifrolumab were upper respiratory and urinary infections as well as shingles. Expert opinion: Anifrolumab is an exciting new therapeutic for SLE patients. Additional analyses of the combined TULIP-1 and TULIP-2 datasets as well as future studies with anifrolumab will generate yet more data in SLE. No doubt anifrolumab will be studied in other diseases where type I interferons play an important role.